Review on CO2 emission from transportation sector in Malaysia - Ghadimzadeh, Azadeh; Ahmad Makmom, Abdullah; Hosea, Mande Kato; Asgari, Nazanin; Shamsipour, Raziyeh; Askari, Arameh; Narany, Tahoora Sheikhy (International Organization of Scientific Research, 2015)
Transportation-related emissions are the dominant contributing source of air pollutants today. Considering the negative impacts of transportation-related emissions on our social and economic environment, extensive efforts have been made by researchers and practitioners attempting to find solutions to reduce the emissions. The present study reviews the current state of GHG emission from transportation section, the measures that have been initiated in Malaysia for GHG emission reduction in transportation sector. Various region’s car ownership, use and emissions are higher than would be predicted on the basis of population or gross domestic product (GDP), and car traffic clogs the streets and pollutes the air of many countries, Furthermore, global carbon emissions from transport, mostly from cars, are predicted to grow threefold by 2030 as both automobile ownership and vehicle use expand. The total emissions level in the developing countries will still be small compared to those of developed countries, but they will not be trivial. Malaysia has committed to reduce its greenhouse gas (GHG) emissions by up to 40% by the year 2020. The fact that transport sector of Malaysia shares a big portion of national GHG emissions; its role is paramount. The review shows deceleration of GHG emission from transportation sector globally and Malaysia in recent years. However, the study reveals that the present measures may not be enough to reduce GHG emission up to the set target. Malaysia needs more prudent strategies for climate-friendly development of transportation to achieve sustainability goals.